Samarium Oxide Based Nanomaterials for Heterogeneous Catalysis - Hodgson, Gregory K. (Université d'Ottawa / University of Ottawa, 2018)
The emergence of unique or enhanced physical, chemical and optical material properties at the nanoscale underlies the swift rise of nanomaterials science over recent decades. Within this interdisciplinary field, catalysis performed by nanomaterials (i.e. nanocatalysis) is one area where differences between nanoscale and bulk material properties offer particularly attractive opportunities for application. The consequent pursuit of viable nanomaterials with unprecedented catalytic activity has inevitably expanded across the periodic table, whereby a number of highly efficient precious metal, metal oxide and composite nanostructured catalysts have been developed for a wide range of synthetic organic and inorganic transformations. The lanthanide series has not been excluded from this search, but is still underrepresented in catalysis despite some rich chemistry and reactivity which sets these elements apart from many other metals. More recently however, the necessary paradigm shift away from commonly utilized but expensive, potentially toxic precious metal catalysts, and toward more sustainable alternatives, has seen an upsurge in the development of novel nanomaterials for heterogeneous catalysis: the general topic of this doctoral thesis. Heterogeneous nanocatalysis offers distinct advantages over homogeneous catalysis. Catalyst recyclability, ease of separation from reaction mixtures, and minimal product contamination all contribute to the higher overall effectiveness of heterogeneous catalysts relative to their homogeneous counterparts. The use of light as an abundant reagent, both in nanomaterial fabrication and for photocatalysis, is another attractive prospect. This dissertation addresses both points, describing the iterative development and application of photochemically-prepared samarium oxide based nanomaterials for heterogeneous catalysis and photocatalysis. Through a series of related peer-reviewed publications and associated commentary, the evolution of the application-driven design of a nanomaterial which is both efficient and effective for a diversity of heterogeneous catalytic and photocatalytic transformations is presented. Major findings include 1) both colloidal and supported samarium oxide nanoparticles can be prepared photochemically and comprise primarily Sm2O3 but may contain localized mixed valences or dynamic surface oxidation states; 2) colloidal samarium oxide nanoparticles possess high activity for Brønsted acid and oxidative catalysis, but recyclability and overall effectiveness is less than optimal due to a combination of polydispersity and size-dependent catalytic activity; 3) a similarly-prepared “second generation” samarium oxide/titanium dioxide nanocomposite presented several advantages over its predecessor, performing highly efficient and effective pure heterogeneous, dual photoredox-Lewis acid catalysis in two different types of synthetically relevant photocyclizations. Effects of different nanoparticle supports, rare insights into the catalytic mechanisms and behaviour of these nanomaterials‒obtained at the single molecule level by innovative application of Total Internal Reflection Fluorescence Microscopy (TIRFM) to catalysis research‒as well as advances in TIRFM data analysis protocols, are also discussed.
Keywords: Nanomaterials; Heterogeneous; Catalysis; Photocatalysis; Samarium; Single-molecule; Fluorescence Microscopy